IDENTIFICATION OF STUDENTS’ ATTITUDES ON MULTIPLE LEARNING INTEREST AND SOCIAL IMPLICATIONS OF SCIENCE SUBJECT - Roro Hoyi; Yolanda Eka Putri; Ngaliman Ngaliman (JURNAL TARBIYAH, 2019)
The purpose of this study was to identify how students' attitudes at SMPN 6 Batanghari toward science subjectby using two indicators, namely: the social implications of science and interest in increasing the time of science learning. This research used a quantitative approach with a survey method and the instrument was an attitude questionnaire. The samplein this study was 143 students at SMPN 6 Batanghari. Data analysis in this study used descriptive statistics. The results obtained showed that the attitudes of students in SMPN 6 Batanghari on the indicator of attitude of interest in increasing the amount of time for learning science can be said to be quite good, and for attitudes the social implications of science can also be said to be good. From the overall results of the data, there were many factors that influence the positive or negative attitudes of students in the science learning process. Thus, the teacher must be able to foster more students’ attitudes in science subject so that students have a positive attitude and can achieve better performance and can provide insight and knowledge to teachers related to student attitudes in the science learning process so that they are able to assist teachers in making lesson plans, methods, models and strategies that fit to the characteristics of students’ attitudes.